In the shadows: Phenomenological choreographic writing. Issue 1 (1st July 2022) - Heimonen, Kirsi; Rouhiainen, Leena
This article introduces a piece of choreographic writing. It likewise discusses the kind of site-specific choreographic process of opening up to what in everyday life is not apparent and left in the shadows that generated the writing. The objective of the choreographic process was to allow the impact of the bodily sense of being in contact with an urban location to permeate the authors' activities in writing. To support this intention, they generated a phenomenologically informed performative score of experimental writing that aims at appreciating the vitality of the sensuous. The first part of the submission presents the actual choreographic writing as an evocative piece of choreography that can be read independently of the second part. This latter part contains an exploration into conceptions about choreography and writing. Here, the article draws specifically on Jean-Luc Nancy's insights to articulate the kind of phenomenological approach the authors engaged in. It aims at establishing their artistic process as a phenomenologically oriented method in expanded choreography and argues that the writing they generated exscribes their encounter with the Hakaniemi bank in Helsinki on a late December day. It likewise details the significance the body bears on their take on choreographic writing and points towards the manner in which this writing contains traces of the inexpressible and non-thinkable.